MECHANICAL PROPERTIES OF STRUCTURAL EPOXY AFTER SIXTEEN MONTHS EXPOSURE TO OUTDOOR TROPICAL ENVIRONMENT - Shukur Abu Hassan; Khairunnisa Mohammad Yunus; Umar Abdul Hanan; Mohd Yazid Yahya; Mat Uzir Wahit; Balqis Omar (PROSIDING SEMINAR NASIONAL CENDEKIAWAN, 2018)
Durability study in regards of epoxy as adhesive which commonly use in current civil industry are still lacking in order to find easy accessible data base. Having validated data to determine its life span will significantly help. The objective of this study is to find out the mechanical properties of Resifix 31 structural epoxy after sixteen (16) months exposure to outdoor tropical environment. The adhesive specimens were cast in a butterfly shaped mould before being exposed to outdoor environment for sixteen (16) months. The exposed specimens were labelled as ESLT-OD16 before being mounted to the Arcan fixture which then attached to the 10kN universal testing machine in tensile mode to determine its shear properties. Microstructure analysis is then performed to study their respective surface fracture and cross-section fracture. The results are then compared to the previous research of control room sample which labelled as ESST-CO06 and sample that exposed to outdoor environment for six (6) months which labelled as ESLT-OD06. The study shows that shear strength and shear modulus of ESLT-OD16 are the lowest when compared to ESST-CO06 which is 61% and 88% respectively.  The study also shows that ESLT-OD16 having 34% of weight loss compared to ESLT-OD06 which is resulting from the dry-wet cycle of the unpredictable outdoor condition.